Gen Z’s loyalty unpacked : The interplay of brand image, service quality, and price on satisfaction and trust (Global Business Management Review (GBMR), 2024)
The Malaysian telecommunications market is exceptionally competitive, compelling companies to innovate, collaborate, and adapt their strategies so as to retain a competitive advantage and enhance customer loyalty. This study investigates the intricate relationships among brand image, service quality, perceived price, customer satisfaction, customer trust, and customer loyalty, with a focus on Gen Z within the Malaysian telecommunications sector. Using a self-administered questionnaire survey, 187 responses were gathered from individuals within the Gen Z cohort. The numerical data was subsequently analysed using the statistical technique of Partial Least Squares-Structural Equation Modelling (PLS-SEM). The empirical results highlight the significant influence of brand image, service quality, and perceived price on customer satisfaction and trust. Moreover, customer satisfaction acts as a vital mediator among these variables, effectively heightening customer loyalty. Interestingly, the impact of customer trust on loyalty, as well as its role as a mediator between brand image, perceived price, service quality, and loyalty, is not significant. This finding suggests that, within the telecommunications context, trust may not serve as a primary driver of loyalty. The study makes significant theoretical contributions to consumer behaviour models by clarifying the complex relationships among the key constructs and highlighting the importance of mediation analysis in understanding customer dynamics. Practically, it advises telecommunications companies to prioritise effective branding, enhance service quality, and implement suitable pricing strategies to boost customer satisfaction and foster loyalty.